Game-based science simulations to support learning and teaching: Science pre-service teachers’ perceptions. - Sheffield, Rachel; Koul, Rekha; Sims, Craig (Brill, 2024)
Science teacher educators have a complex role in preparing future science teachers, giving them the content and pedagogical and technological knowledge. This research examines using a gamified laboratory simulation tool (Labster), where access was given to a cohort of science pre-service teachers (pst s) in the third year of their Initial Teacher Education for a semester. A mixed-method approach was adopted to generate data for this case study. Schulman’s pedagogical content knowledge provided the theoretical background, whilst framework was deployed to identify factors in implementing Labster, including usability, motivation, and perceived use. The data determined that despite the ongoing engagement and interest in games and gamification in the wider community, the perceived engagement and interest were not reflected in the responses of the undergraduate science pst s in the study. pst s reported that they did not feel that it improved their content knowledge.